Kapasitas Dinas Lingkungan Hidup dalam Pengelolaan Sampah di Tempat Pemrosesan Akhir (TPA) Kabupaten Labuhanbatu - Riski Prayuda; Zoraya Alfathin Rangkuti (Lembaga Intelektual Muda Maluku, 2025)
Labuhanbatu Regency is among the top five regions producing the largest waste in North Sumatra with a total of 130,188 tons. This study aims to analyze the capacity of the Labuhanbatu Regency Environmental Agency in waste management, especially at the Final Processing Site (TPA). The study used a descriptive method with a qualitative approach through observation techniques, and in-depth interviews with officials and field officers, direct observation at the TPA and TPS locations, and documentation in the form of official archives, regional regulations, annual reports, field photographs, and waste management statistics from the DLH and SIPSN KLHK. Data analysis was conducted qualitatively using Hall et al.'s capacity theory, which emphasizes the ability of an organization to carry out its functions by considering limiting factors. Data analysis was conducted qualitatively using capacity theory. The results of the study indicate that the capacity of the Labuhanbatu Regency Environmental Agency in waste management is still not optimal. Infrastructure and process capacity are inadequate due to the limited number of garbage trucks. Furthermore, planning and development capacity remains weak, as evidenced by the unrealized plan to add a new landfill. Therefore, institutional capacity building, infrastructure improvements, and strategic planning are needed to ensure optimal and sustainable waste management in Labuhanbatu Regency